The relationship between psychological contract fulfilment on turnover intention: A conceptual paper - Zhao, Yu; Hasan, Norhafizah Abu; Arshad, Rasidah; Abdullah, Nur Atiqah (Edelweiss Applied Science and Technology, 2025)
This conceptual paper explores the influence of psychological contract fulfillment on turnover intention, mediated by thriving at work and job crafting. Grounded in Psychological Contract Theory and Self-Determination Theory, it proposes a conceptual framework to explain these dynamics. In today’s rapidly changing work environment, organizations face increasing difficulty in retaining skilled employees. The presence of high turnover rates has been demonstrated to have a deleterious effect on organizational stability and to result in the incurrence of considerable financial and operational costs for the affected institutions. However, existing literature lacks a comprehensive understanding of how psychological contract fulfillment, thriving at work, and job crafting interact to influence turnover intention. This paper, developed through archival research, draws on literature published between 2000 and 2025 from Web of Science, ProQuest, JSTOR, and Google Scholar. It posits that psychological contract fulfillment—employees’ perception of employers keeping their promises—directly reduces turnover intention. Moreover, thriving at work, characterized by vitality and learning, and job crafting, referring to employees’ proactive role redesign, are proposed as mediators that reinforce this effect. The findings are expected to contribute to more effective employee retention strategies and support organizational sustainability.